“Another spirit, other thoughts, another colouring”: Performances of Race in Antonín Dvořák’s Symphony No. 9 From the New World - Sikand-Youngs, Nathaniel (Hungarian Journal of English and American Studies, 2020)
The Czech composer Antonín Dvořák wrote his Symphony No. 9 in E minor (From the New World) in 1893 while he served as the director of the National Conservatory of Music in New York City. In the work, he intended to portray the US and establish its musical vernacular. Dvořák believed that a truly American school of classical composition must evoke the character of its indigenous and folk music which he identified with Native American and African American styles. Through a musicological analysis, the essay offers cultural criticism of how the symphony represents these musical traditions and, in turn, the indigenous and black peoples who produced them. I argue that the symphony alludes to Native and black Americans in inaccurate and, at times, objectionable terms, but does so through a musical aesthetic that warrants a more nuanced conclusion about the racial content of the composition. (NS-Y)